Together is better : a little book of inspiration - Sinek, Simon (Portfolio/Penguin, 2016)
Filled with inspirational quotes, this richly illustrated fable tells the story of three kids who go on a journey to a new playground and take a stand for what they believe. The story is a metaphor for anyone looking to make a change or wondering how to pursue their dreams. And the message is simple: relationships -- real, human relationships -- really, really matter. The stronger our relationships, the stronger the bonds of trust and cooperation, the more we can accomplish and the more joy and fulfillment we get from our work and personal lives. The three heroes are archetypes who represent us all at various points in our lives. Their main challenge is the same one we face every day: How can we find the things we're looking for? According to Sinek, if we each do our part to help advance a shared vision, we can build the world we imagine.